(untitled) (Forum Penelitian Agro Ekonomi, 2024)
An effective and efficient national food security strategy and policy can only be formulated using an appropriate paradigm. Food security paradigm evolves as food security context changes and in line with development of scientific understanding of the issue. This paper discusses evaluation of the food security paradigm and their application in designing strategy and framework of food security policy in Indonesia. It is shown that the national food sufficiency-oriented policy belongs to the food availability approach which has been empirically proven can not assure household or individual food security. The more appropriate paradigm is the food entitlement approach. Based on this paradigm, national food security strategy and policy should be designed comprehensively that includes food availability, access and utilization dimensions, and risk mitigation related to the three dimensions in an integrated macro-micro scale.